2016
DOI: 10.3390/ma9120978
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Characteristics of Chemically Treated Water-Repellent Kaolin

Abstract: Water-repellent soils have a potential as alternative construction materials that will improve conventional geotechnical structures. In this study, the potential of chemically treated water-repellent kaolin clay as a landfill cover material is explored by examining its characteristics including hydraulic and mechanical properties. In order to provide water repellency to the kaolin clay, the surface of clay particle is modified with organosilanes in concentrations (CO) ranging from 0.5% to 10% by weight. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Ugwu et al (2013) discuss the reaction chemistry of Nanomaterial with the aim of facilitating a better understanding of the fundamental science that underpins the observed changes in soil geotechnical properties (i.e., hydrophobicity, plasticity, and swell potential). Choi et al (2016) investigated the potential of chemically treated water-repellent kaolin clay as a landfill cover material is explored by examining its characteristics including hydraulic and mechanical properties. Athulya et al (2017) Investigated effective utilization of steel slag, a by-product from the steel industry, as construction material in highway pavement layers so that the industrial wastes can be used and disposed properly with reduction in environmental impact as well as the FIGURE 1 | Active soil zone and layout of sampling i.…”
Section: Review Of Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Ugwu et al (2013) discuss the reaction chemistry of Nanomaterial with the aim of facilitating a better understanding of the fundamental science that underpins the observed changes in soil geotechnical properties (i.e., hydrophobicity, plasticity, and swell potential). Choi et al (2016) investigated the potential of chemically treated water-repellent kaolin clay as a landfill cover material is explored by examining its characteristics including hydraulic and mechanical properties. Athulya et al (2017) Investigated effective utilization of steel slag, a by-product from the steel industry, as construction material in highway pavement layers so that the industrial wastes can be used and disposed properly with reduction in environmental impact as well as the FIGURE 1 | Active soil zone and layout of sampling i.…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…In order to study the magnitude of possible swell in the clay, the test suggested by Sivapullaiah et al (1996) was followed (Bailey, 1980;Sivapullaiah, 1996; ASTM Standard Test Methods for One-Dimensional Swell or Settlement Potential of Cohesive Soils, 1999;Das, 1999;Venkatramaiah, 2006;Maghsoudi and Dahooei, 2009;Okagbue, 2014;Choi et al, 2016;Syed et al, 2018). This appears to give a better indication for the swelling potential of clayey soil with a mass of about 10 g. The soil mass was well pulverized and transferred into a 100 ml graduated jar containing distilled water.…”
Section: -H Free Swell Test For Classificationmentioning
confidence: 99%
“…Designed applications to improve environmental quality through heavy metal ions removal have recently emerged. Moreover, the versatility of the kaolin clay support to be chemically modified induces its application to produce new materials available for removing contaminates from water and soils [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of soil water repellency in geotechnical engineering has been recognized due to its significant effect on water infiltration, evaporation, soil strength, and soil stability [6,7]. Potential applications of water repellent soils (WRS) in ground infrastructure include hydraulic barriers for embankments, landfills, flood defences and other applications [8][9][10]. The assessment of water repellency hence becomes essential.…”
Section: Introductionmentioning
confidence: 99%